Safety glasses - Nik Roslee, Nik Mohamad Idzham; Zulkarnain, Luqman Nain; Othman, Siti Amira (Penerbit UTHM, 2020)
Safety glasses are one of the vital safety tools as to protect the sight from harm. From the workshop tasks to the scientific uses, the safety glasses contribute tremendously in the safety part of human lifestyle. In fact, eyes are the most important sensory organ that have varies of senses. Thus, the eyes can be considered as sensitive organ that easily exposed to the danger. Unlike the other part of the body, our eyes do not have protective layer as efficient as the skin. In addition, the eyelashes only capable of preventing small particles enter our eyes and unable to protect from the debris particle. Hence, we need an extra protective eyewear to enclose protection from incoming hazards.